LEVELS OF PHYSICAL ACTIVITY AND FITNESS IN NORMAL-WEIGHT AND OVERWEIGHT CHILDREN (Fiep Bulletin - online, 2014)
The levels of daily physical activity are reduced during preadolescence and this predisposes young people to overweight and obesity [1,2]. The levels of physical fitness of young people are in relation to BMI [3]. The aim of the study was to examine the physical activity levels and motor performances in relation to BMI . The Physical Activity Questionnaire for Children (PAQ_C) [4] and tests on standing long jump and 20-m sprint[5,6], have been completed by a sample of 161 boys and 141 girls, aged 11 to 12 years, divided into two groups, normal weight and overweight / obese, according to the cut off of Cole [7]. Apart from the descriptive statistics (M±DS), Student’s T Test was carried out, in order to highlight the significant differences within the group. The significativity index was set to p
Keywords: physical activity levels; physical fitness; physical education; obesity; school.